2013
DOI: 10.3382/ps.2013-03441
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine, anserine, creatine, and inosine 5′-monophosphate contents in breast and thigh meats from 5 lines of Korean native chicken

Abstract: The aim of this study was to examine the effect of chicken line on the contents of endogenous compounds, including carnosine, anserine, creatine, and inosine 5'-monophosphate (IMP), in breast and thigh meats from 5 lines of Korean native chicken for the development of high-quality meat breeds. Additionally, the effects of sex (male or female) and meat type (breast or thigh meat) were examined. In total, 595 F1 progeny [black: 90 (male: 45, female: 45); gray-brown: 110 (male: 52, female: 58); red-brown: 136 (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
132
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(150 citation statements)
references
References 43 publications
16
132
0
2
Order By: Relevance
“…pH value also has an influence in degradation rate for nucleotide contents as acidic pH inhibits the activities of AMP deaminase and promotes degradation rate of IMP to inosine (Jung et al, 2013;Vani et al, 2006), however, no significant differences were observed for both breeds and sexes in pH of 5.90∼5.93 (data not shown).…”
Section: Nucleotide Contentsmentioning
confidence: 95%
See 1 more Smart Citation
“…pH value also has an influence in degradation rate for nucleotide contents as acidic pH inhibits the activities of AMP deaminase and promotes degradation rate of IMP to inosine (Jung et al, 2013;Vani et al, 2006), however, no significant differences were observed for both breeds and sexes in pH of 5.90∼5.93 (data not shown).…”
Section: Nucleotide Contentsmentioning
confidence: 95%
“…In addition, these compounds are varied with breed, sex, age, meat portion and cooking state, etc (Joo et al, 2013;Jung et al, 2013;Karasawa et al, 1989;Vani et al, 2006). Duck meat is getting attention from the consumers, in particular, in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Betaine 은 삼투압조절 효과를 갖고 있으며 조직내의 methyl donor 로서 methionine 합성을 유도하는 역할을 한다 (Alirezaei et al, 2012). 따라서 이러한 생리활성 물질을 많이 함유하고 있는 식 육은 영양학적 품질이 우수한 것으로 여겨지고 있다 (Jung et al, 2013).…”
Section: 최근 적색육 섭취에 따른 대장 및 결장암과 같은 여러 질병의 발생 가능성이 증가할 수 있다는 일부 연구unclassified
“…또한 숙성은 식육 내 함유되어 있는 효소들의 작용을 통해 탄수화물. 단백 질 및 핵산 등의 성분들을 저분자 물질로 분해시킴으로써 유리 아미노산, 펩타이드, 비단백태 질소 화합물, 단 당류 및 인산 화합물 등과 같은 저분자 풍미 전구물질들을 생성시켜 고기의 풍미를 증진시킨다 (Reina et al, 2014 (Jung et al, 2013;Humada et al, 2014). 또한 산화로 인하여 생성되 는 alcohol, aldehyde 및 ketone 등의 물질들이 체내 DNA를 손상시키거나 암을 유발하며 노화와도 관련이 있다고 보고되고 있다 (Lee et al, 1999;Kang et al, 2013).…”
Section: 최근 적색육 섭취에 따른 대장 및 결장암과 같은 여러 질병의 발생 가능성이 증가할 수 있다는 일부 연구unclassified
“…There is a growing interest in the use of native chicken breeds for the production of chicken meat in many countries because native chicken meats have properties such as high protein content, low fat content, unique flavor and texture compared with those of broiler chicken meat (Fanatico et al, 2007;Jaturasitha et al, 2008;Jayasena et al, 2013;Jung et al, 2013). In addition, the conservation of native chicken breeds is considered important because the increasing use of broiler chickens with rapid growth properties has resulted in the loss of genetic diversity among chicken breeds (Zanetti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%